Human Development as flows of mobility: Perspectives from the Bulawayo-Johannesburg trends - Zikhali, Whitehead (Advances in Social Sciences Research Journal, 2018)
Studies of migration experience tend to be trapped in situ where focus is on either the place of origin or the destination. Using the mobilities paradigm, this paper reveals that migrants does not merely move from origin to destination through a void devoid of meaning but engage in various negotiations and exchanges of meaning both with other people and with spaces and objects. In the process, various notions of development are derived. The mobilities paradigm is field of enquiry which comprises of ‘studies of corporeal movement, transportation and communication infrastructures, capitalist spatial restructuring, migration and immigration, citizenship and transnationalism, and tourism and travel’ (Hannam et al., 2006, p.9–10). The study shows that development is much broader than economic and infrastructural progress, encompassing social and security needs as well. This has real implications for migration because it suggests that migrants are no merely drawn from backward places to advanced zones. Instead, they move between places to attain their ideal notion of development, a notion which may be situated in both sending and receiving places. In the study, Johannesburg is an economic attraction while Bulawayo poses social and security comfort. The result is that migrants relate with both places as sites of development, with development assuming various meanings in all contexts.